Rendimiento reproductivo en cruzamientos entre razas tradicionales de aves productoras de huevo y carne - Revidatti, F. (2005)
In this work we evaluate different variables in relation with the reproductive output in two traditional breed chicken types one of them semi-heavy for egg production (Negra and Rubia INTA) and the other one heavy whose offsprings are destined to meat chicken production (Campero INTA). We found significative differences in the settables egg number (191 and 110 eggs per hen per year) in the fertility percent (93 and 88) in the hatchability (88 and 83) and in the chick number per hen per year (158 and 82) between semi-heavy an heavy chickens respectively. These results agree with the references in relation with reproductive fitness in laying and meat type chickens.